Is there a role for transcatheter left atrial appendage occlusion?. (December 2009) - Block, Peter C
For patients with atrial fibrillation, successful warfarin therapy is difficult in clinical practice. Thus, it seems logical to find alternative therapies to chronic anticoagulation. The major source of thromboembolism in such patients is the left atrial appendage, and occlusion of the appendage with transcatheter devices is feasible, reduces anticipated stroke rates and has been found to be noninferior to warfarin therapy in a large, randomized trial. Trials with new devices are planned. In light of the current data, how patients with atrial fibrillation who need warfarin, who are either at risk with anticoagulation or who desire not to undergo warfarin therapy should best be treated is not clear. Hopefully, with more experience and longer term outcomes of clinical trials, these issues will finally be laid to rest.